2022
DOI: 10.3389/fcimb.2022.962059
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome genetic variants are associated with tuberculosis, HIV-1 infection, and TB/HIV-immune reconstitution inflammatory syndrome outcomes

Abstract: BackgroundTuberculosis (TB) and AIDS are the leading causes of infectious diseases death worldwide. Here, we investigated the relationship between from single nucleotide polymorphisms (SNPs) of the NLRP3, CARD8, AIM2, CASP-1, IFI16, and IL-1β inflammasome genes, as well as the profiles of secreted proinflammatory cytokines (e.g., IL-1β, IL-18, IL-33, and IL-6) with the TB clinical profiles, TB-HIV coinfection, and IRIS onset.MethodsThe individuals were divided into four groups: TB-HIV group (n=88; 11 of them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The same group from Brazil investigated the relationship between the SNPs of inflammasome genes and the onset of TB-IRIS. The study findings reveal the association of a higher risk of IRIS with the CT genotype or carrier allele T in the AIM2 gene, thereby confirming the involvement of polymorphisms in genes belonging to the innate immunity in the onset of TB-IRIS [ 60 ]. A recent study evaluated several blood transcriptomic TB signatures as tools to predict TB-IRIS before starting ART and the diagnosis of IRIS among a HIV-infected pediatric cohort initiating ART, and they demonstrated a modest but significant prognostic and diagnostic profile [ 68 ].…”
Section: Newer Host Genetic Markers To Predict Tb-irissupporting
confidence: 54%
See 2 more Smart Citations
“…The same group from Brazil investigated the relationship between the SNPs of inflammasome genes and the onset of TB-IRIS. The study findings reveal the association of a higher risk of IRIS with the CT genotype or carrier allele T in the AIM2 gene, thereby confirming the involvement of polymorphisms in genes belonging to the innate immunity in the onset of TB-IRIS [ 60 ]. A recent study evaluated several blood transcriptomic TB signatures as tools to predict TB-IRIS before starting ART and the diagnosis of IRIS among a HIV-infected pediatric cohort initiating ART, and they demonstrated a modest but significant prognostic and diagnostic profile [ 68 ].…”
Section: Newer Host Genetic Markers To Predict Tb-irissupporting
confidence: 54%
“…Various studies have evaluated the potential role of various inflammatory cytokines and acute-phase reactants as biomarkers of TB-IRIS and the findings, though encouraging, are not concrete enough to be considered clinically useful now. Elevated levels of CRP, IL-6, IL-18, IP-10, IL-33, IFN-γ, and sCD14 individually or in combination have been investigated extensively as predictors for paradoxical TB-IRIS [ 15 , 50 , 57 , 58 , 59 , 60 ]. A prospective observational study from Botswana evaluated 26 plasma biomarkers in baseline specimens and revealed an association between TB-IRIS and lower growth factors such as IL-3, Th1 cytokine responses and low levels of IL-17 [ 16 ].…”
Section: Challenges In Predicting And/or Diagnosing Tb-irismentioning
confidence: 99%
See 1 more Smart Citation
“…extensively as predictors for paradoxical TB-IRIS. [15,[50][51][52][53][54] A prospective observational study from Botswana evaluated 26 plasma biomarkers in baseline specimens and revealed an association between TB-IRIS and lower growth factors such as IL-3, Th1 cytokine responses and low levels of IL-17. [16] A study that investigated the role of IFN-γ release assays in response to mycobacterial antigens as a diagnostic marker for TB-IRIS did not reveal any significant differences between those who developed TB-IRIS and those who did not.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…The study findings reveal the association of a higher risk of IRIS with the CT genotype or carrier allele T in the AIM2 gene, thereby confirming the involvement of polymorphisms in genes belonging to the innate immunity in the onset of TB-IRIS. [54] A recently study evaluated several blood transcriptomic TB signatures as tools to predict TB-IRIS before starting ART and diagnosis of IRIS among a HIV-infected pediatric cohort initiating ART and they demonstrated a modest but significant prognostic and diagnostic profiles. [62] In a pilot metabolomic study of TB-IRIS, Silva et al found that pathways involving the participation of arachidonic acid, linoleic acid, and glycerophospholipid metabolism are relevant markers in patients who are at increased risk of developing TB-…”
Section: Newer Host Genetic Markers To Predict Tb-irismentioning
confidence: 99%